Psychosocial Effect of Parental Conflicts on Youngsters’ Behavior Growth (Journal of Social Sciences Review, 2023)
There is no relationship entirely free from conflict and disagreement. Children suffer when their parents fight. When parents argue, children show sadness. Their reactions are fear, anxiety, anger, sadness, and depression, and they are at a high risk of worsening. The main goal was to examine parental conflict and how it hurts the growth of children's behavior in demographic and cultural contexts. The research was done in the urban areas of District Lahore, Punjab, Pakistan. A multistage sampling method was used to get a sample of 400 respondents between the ages of 10 and 19 who had both parents. To find out about the research goals, a well-made questionnaire was made. Data analysis, based on univariate and bivariate (chi-square and gamma text), was used to examine the responses and how they were related to the destructive effect on behavior growth. The results of a quantitative study showed that most people who had a lot of fighting between their parents at home had many bad things happen to them as they grew up. The chi-square value is significant at (0.000). In the sample, insufficient behavior growth was strongly linked to age, family type, number of siblings, the reason for parental conflict, level of parental competition, drug use, and health problems. It is suggested that parents understand that their kids are hurting when they see their parents fighting. A psychologist or counsellor should ensure that fighting between parents doesn't break the kids.
Keywords: Interparental Harmony; Parent-Youngster Relationship; Demographic Factors; Psychological Effects; Character Growth; Emotional Security; Cultural Conditions